2018
DOI: 10.1038/s41598-018-23874-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals that auxin homeostasis influences the eighth internode length heterosis in maize (Zea mays)

Abstract: Ear height is an important maize morphological trait that influences plant lodging resistance in the field, and is based on the number and length of internodes under the ear. To explore the effect of internodes on ear height, the internodes under the ear were analysed in four commercial hybrids (Jinsai6850, Zhengdan958, Xundan20, and Yuyu22) from different heterotic groups in China. The eighth internode, which is the third aboveground extended internode, exhibited high-parent or over high-parent heterosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Transcriptome and other omics have provided powerful strategies for elucidating the molecular basis of heterosis in diverse plants [ 12 , 15 , 20 ]. In the present study, the transcriptome data confirmed that the hybridization activated more genes in the hybrid broccoli with obviously yield heterotic trait than those in their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome and other omics have provided powerful strategies for elucidating the molecular basis of heterosis in diverse plants [ 12 , 15 , 20 ]. In the present study, the transcriptome data confirmed that the hybridization activated more genes in the hybrid broccoli with obviously yield heterotic trait than those in their parents.…”
Section: Discussionmentioning
confidence: 99%
“…This similitude seems to be the result of duplication events among the genes and a domain rearrangement due to alternative splicing 63,64 , which has modified the number of ARF genes in different species 53,62 . An expression analysis in silico of ZmARF27 showed that this gene in maize is mainly expressed in the seed, tassel and ear 59 , tissues affected by auxin concentration [65][66][67] . For instance, Chen et al 65 found that there is a positive correlation between IAA concentration and ear height.…”
Section: Discussionmentioning
confidence: 99%
“…An expression analysis in silico of ZmARF27 showed that this gene in maize is mainly expressed in the seed, tassel and ear 59 , tissues affected by auxin concentration [65][66][67] . For instance, Chen et al 65 found that there is a positive correlation between IAA concentration and ear height. On the other hand, Erkoyuncu et al 67 reported that high concentrations of 2,4-D increase callus formation in maize embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decrease in abundance of indole-3-acetaldehyde oxidase protein could have influenced IAA biosynthesis, which is important for rapid seed germination in F 1 hybrids. Recently, Chen et al (2018) using proteomic analysis revealed the importance of auxin homeostasis on eighth internode length heterosis in maize.…”
Section: Deps Are Associated With Different Cellular Processesmentioning
confidence: 99%